Implementation of Cognitive Behavioral Therapy (CBT) Counseling in Drug Abuse Prevention Efforts for At-Risk Students at SMPN 8 Tipo, Palu City - Fitri Ramadani; Moh. Rizkyadityaanshari; Reygina Anggraini; Bambang Hermawan; Nuraiman Nuraiman (Abdi Masyarakat, 2026)
This community service-based research study aims to analyze the effectiveness of counseling in promoting behavioral change, as well as the potential effectiveness of Cognitive Behavioral Therapy (CBT) counseling in preventing drug abuse among students at SMPN 8 Tipo, Palu City. This counseling program was implemented by the National Narcotics Agency (BNN) of Palu City for students identified as being at risk of drug abuse. The study employed a quantitative approach with a quasi-experimental one-group pretest–posttest design. The study sample consisted of 10 students. Data collection was conducted using a Likert scale questionnaire that measured risky drug abuse behavior, attitudes toward drugs, and coping skills. Data analysis was performed using a paired-sample t-test to compare scores before and after the intervention. The results of the study showed positive changes in all measured variables. Risky drug abuse behavior decreased by 43%, while attitudes toward drugs improved by 20% and coping skills increased by 33%. Statistically, the difference between the pretest and posttest was significant (p < 0.001). Additionally, observational results indicated improvements in students’ social behavior, such as increased discipline, communication, and engagement in positive activities. These findings suggest that the implementation of CBT counseling has potential as a preventive approach to reducing the risk of drug abuse among adolescents in school settings. The success of the program’s implementation was also supported by the involvement of the school, families, and counselors.